ANALYSIS OF THE EFFECTIVENESS OF EMPLOYEE PERFORMANCE APPRAISAL THROUGH EMPLOYEE PERFORMANCE TARGETS (SKP) - Setyawati, Reny Hajar; Rindaningsih, Ida (International Journal Multidisciplinary (IJMI), 2024)
Employee performance appraisal in the public sector is an important element of human resource management. The aim is to measure the achievement of work targets and provide constructive feedback to improve individual and organizational performance. Employee Performance Target (SKP) is an evaluation tool used in employee performance management in the public sector. SKP is used to measure the achievement of work targets and provide constructive feedback to improve individual and organizational performance. However, the implementation of SKP does not always run well and optimally. Some factors that can hinder the effectiveness of SKP include the lack of understanding and competence of employees in preparing SKP, lack of support and supervision from superiors, and lack of employee involvement and participation in the performance appraisal process. The research method we used involved a qualitative approach focused on literature study. The qualitative approach was chosen because it can provide an in-depth and contextual understanding of the phenomenon of employee performance appraisal through Employee Performance Targets (SKP). The results of this study show that there are several weaknesses found in the application of SKP, namely less objective, less competent, less active, less productive, and less responsible. In addition, there are several challenges in the application of SKP, namely less effective, less productive, less competent, less responsible, and less efficient. In assessing employee performance, SKP has the advantage of increasing employee motivation, productivity, efficiency, and effectiveness. However, its application still faces challenges in the aspects of effectiveness, productivity, competence, responsibility, and efficiency. Keywords: Effectiveness, Employee Performance Appraisal, Employee Performance Targets (SKP)